COMPARISON BETWEEN β-CYCLODEXTRIN AND MALTODEXTRIN AS ENCAPSULATED AGENTS OF VACUUM DRIED NUTMEG SEED OLEORESIN - Victoria Kristina Ananingsih; Bernadeta Soedarini; Sumardi Sumardi; Bong Y.A. Santoso; Bernardine Agatha Adi Konstantia (Soegijapranata Catholic University, 2024)
Nutmeg is a spice plant native to Maluku, Indonesia. Nutmeg seed oleoresin is widely applied in the food and beverage industry because of its unique flavor and aroma. However, oleoresin has less stable properties to heat, oxygen, and light. Therefore, an encapsulation process is needed to protect oleoresin. The extraction of nutmeg seed oleoresin is carried out by ultrasonication method (Ultrasound Assisted Extraction) because of its lower energy consumption, shorter operating time, and can be carried out at low temperatures and pressures, making it suitable for the extraction of compounds that are sensitive to high temperatures. Nutmeg seed oleoresin encapsulation was carried out by the vaccuum drying method using two types of encapsulants (β-cyclodextrins and maltodextrin) at two treatment levels (7 grams and 10 grams) with two levels of stirring time (5 minutes and 15 minutes). This study aims to study the comparison between β-cyclodextrin and maltodextrin as encapsulated agents of vacuum dried nutmeg seed oleoresin. Trapped oil was higher on β-cyclodextrin encapsulation than maltodextrin. Moreover, the antioxidant activity of microencapsulates was higher in β-cyclodextrin encapsulant than maltodextrin. The microencapsulate with the best trapped oil value was obtained in the treatment of 10 gram β-cyclodextrin with 15 minutes stirring time which produced 17.5% trapped oil. This treatment resulted in antioxidant activity of 87.06%.